European continuing engineering education : conceptualizing the lessons learned. - Lappalainen, Pia, ....- (Brussels : SEFI, 2009)
This book is an attempt to systematize and conceptualize the phenomena prevalent in today's continuing engineering education (CEE). The field abounds in efforts to learning in engineering. It was about time the multitude of endeavors was organized into a compilation that would illustrate the best theories and practices, as well as roadmap the future. The book digs into the impacts of technological change on the role of universities and the third mission both towards society and at the university-industry interface. Continuing professional development is addressed through experiences from the use of virtual learning environments, e-learning, corporate in-house training, and ICTenabled blended learning, but also through the challenges posed by responsiveness to student needs, transparency, accountability and accreditation. In this publication, lifelong learning is viewed not only as a chain of activities promoting traditional technical expertise but as a constant process of personal and professional development also in the area of social abilities.